230Th/U dating of Last Interglacial brain corals from Bonaire (southern Caribbean) using bulk and theca wall material. (1st April 2016) - Obert, J. Christina; Scholz, Denis; Felis, Thomas; Brocas, William M.; Jochum, Klaus P.; Andreae, Meinrat O.
Abstract: We compared the suitability of two skeletal materials of the Atlantic brain coral Diploria strigosa for 230 Th/U-dating: the commonly used bulk material comprising all skeletal elements and the denser theca wall material. Eight fossil corals of presumably Last Interglacial age from Bonaire, southern Caribbean Sea, were investigated, and several sub-samples were dated from each coral. For four corals, both the ages and the activity ratios of the bulk material and theca wall agree within uncertainty. Three corals show significantly older ages for their bulk material than for their theca wall material as well as substantially elevated 232 Th content and ( 230 Th/ 238 U) ratios. The bulk material samples of another coral show younger ages and lower ( 230 Th/ 238 U) ratios than the corresponding theca wall samples. This coral also contains a considerable amount of 232 Th. The application of the available open-system models developed to account for post-depositional diagenetic effects in corals shows that none of the models can successfully be applied to the Bonaire corals. The most likely explanation for this observation is that the assumptions of the models are not fulfilled by our data set. Comparison of the theca wall and bulk material data enables us to obtain information about the open-system processes that affected the corals. The corals showing apparently older ages for their bulk material were probably affected by contamination with a secondary (detrital) phase. The most likely source of the detrital material is carbonate sand. The higher ( 230 Th/ 232 Th) ratio of this material implies that detrital contamination would have a much stronger impact on the ages than a contaminant with a bulk Earth ( 230 Th/ 232 Th) ratio and that the threshold for the commonly applied 232 Th reliability criterion would be much lower than the generally used value of 1 ng g −1 . The coral showing apparently younger ages for its bulk material was probably influenced by more than one diagenetic process. A potential scenario is a combination of detrital contamination and U addition by secondary pore infillings. Our results show that the dense theca wall material of D. strigosa is generally less affected by post-depositional open-system behaviour and better suited for 230 Th/U-dating than the bulk material. This is also obvious from the fact that all ages of theca wall material reflect a Last Interglacial origin (∼125 ka), whereas the bulk material samples are either substantially older or younger. However, for some corals, the 230 Th/U-ages and activity ratios of the bulk material and the theca wall samples are similar. This shows that strictly reliable 230 Th/U-ages can also be obtained from bulk material samples of exceptionally well-preserved corals. However, the bulk material samples more frequently show elevated activity ratios and ages than the corresponding theca wall samples. Our findings should be generally applicable to brain corals (Mussidae) that are found in tropical oceans worldwide and may enable reliable 230 Th/U-dating of fossil corals with similar skeletal architecture, even if their bulk skeleton is altered by diagenesis. The 230 Th/U-ages we consider reliable (120–130 ka), along with a recently published age of 118 ka, provide the first comprehensive dating of the elevated lower reef terrace at Bonaire (118–130 ka), which is in agreement in timing and duration with other Last Interglacial records.